Structural and electrical properties of Li4.08+xZn0.04AlxSi0.96-xO4 ceramic electrolyte - Adnan, S.B.R.S.; Mohamed, N.S. (2015)
In this paper, we report the effect of Al3+ substitutions to the structural and electrical properties of Li4.08Zn0.4Si0.96O4 ceramic electrolyte. X-ray diffraction was applied to study the structural properties such as crystalline phase, lattice parameter and unit cell volume of the solid electrolytes. The electrical properties of the compounds measured by Ac impedance as a function of frequency in the range between 0.1 Hz to 10 MHz and in temperature range between 473 K to 773 K. The optimal value of the total conductivity were reached at x = 0.03 measured at 773 K. This result indicates that the substitutions of Al3+ in the Li4.08Zn0.4SiO4 structure improved the conductivity due to the enhancement of Li+ ion concentration and mobility.